Penerapan Model Pembelajaran Team Game Tournament Untuk Meningkatkan Motivasi Belajar Siswa Dalam Pelajaran Pkn - Devy, Afriza Anggita (Prosiding University Research Colloquium, 2021)
Learning motivation in learning is very important to note because it is one of the main components. Learning motivation is low because students are not interested or enthusiastic in participating in lessons, especially lessons that require a high level of understanding, one of which is Citizenship Education (PKn). In lessons that require a fairly high level of understanding, the teacher should be able to package the learning well so that students do not feel bored, such as using a fun learning model for students so that learning motivation will increase and achievement will also increase. One of the fun learning models, especially for Civics Education lessons, is the Team Game Tournament Type Cooperative Learning Model (TGT). This model is suitable for lessons that require students to have a good understanding because in this model students are also asked to understand the material but packaged in a different way. games so that the material can be remembered by students. A teacher must also have creativity and innovation in managing the learning process, for example in applying suitable models, methods, and strategies to support the learning process. Especially in lessons that require students to become lessons that are considered boring such as Civics so that the teacher’s task is to manage the learning process as attractively as possible which makes students excited to follow the learning process.